Hydrokinezotherapy as the cause of physical rehabilitation of children of preschool age with cerebral paralysis of spastic form. - Baybuza I.V (Kharkov National Pedagogical University, 2011)
In this work is considered effective influences of physical exercises in water. The dynamics of development of functional indexes is shown by the kardio-respirator and kinesthesia systems. In an experiment took part 15 children of preschool age with the cerebral paralysis of spastic form. It is well-proven that the most substantial changes happened at the estimation of indexes of dynamic force of muscles and goniometry of lower limbs. Leaning against the got results, it is possible to recommend a hydrokinezotherapy in treatment of patients with this pathology.